Longterm temporal analysis of vegetation cover and soil use on Ilha de Mosqueiro, Belém, Pará, Amazonian Brazil - Larissa de Carvalho Lima; Alberto Bentes Brasil Neto; Cassio Rafael Costa dos Santos; Aline Nascimento Braga; Suany Couto Teixeira Nunes (Agro@mbiente On-line)
Assessing the dynamics of land use is important in providing quantified estimates of the extent of ecosystem change, and so and structured planning to reduce its environmental and social impacts. The objective of the current study was to analyze the dynamics of vegetation and soil use on Ilha de Mosqueiro, Belém, Pará State, northern Brazil, between 1984 and 2014, via digital image processing. For this purpose, satellite images of Ilha de Mosqueiro (orbit/point 224/62) were used. These comprised of Landsat 5 Satellite, Sensor TM, images for the years 1984, 1996 and 2008, and 2014 images from the Landsat Satellite 8, OLI sensor. These images were processed so as to classify and determine the area occupied by the following classes: dense vegetation, secondary vegetation, low growth, exposed soil, urban area and other. There was a continuous reduction of the dense vegetation class between 1984 and 2008; this accounted for 67.8% of the total area the Ilha de Mosqueiro in 1984, and 31% in 2008. At the same time the class open soil showed continuous growth across all evaluated periods, representing 2.25% of land cover in 1984, increasing to 2.33% and 4.20%, in 1996 and 2014, respectively. Between 1984 and 2014, there was a great increase in the class urban area, generally associated with the generation of environmental problems, due to irregular occupation and lack of environmental and urban management of the island.